Differences and allometric relationships among assimilative branch traits of four shrubs in Central Asia - Meng, Huan-Huan; Yin, Ben-Feng; Li, Yong-Gang; Zhou, Xiao-Bing; Zhang, Yuan-Ming; Tao, Ye; Zhou, Duo-Qi (Frontiers in Plant Science, 2022)
Shrubs play a major role in maintaining ecosystem stability in the arid deserts of Central Asia. During the long-term adaptation to extreme arid environments, shrubs have developed special assimilative branches that replace leaves for photosynthesis. In this study, four dominant shrubs with assimilative branches, namely Haloxylon ammodendron, Haloxylon persicum, Calligonum mongolicum, and Ephedra przewalskii, were selected as the research objects, and the dry mass, total length, node number, and basal diameter of their assimilative branches and the average length of the first three nodes were carefully measured, and the allometric relationships among five traits of four species were systematically compared. The results indicated that: (1) Four desert shrubs have different assimilative branches traits. Compared with H. persicum and H. ammodendron, C. mongolicum and E. przewalskii have longer internodes and fewer nodes. The dry mass of H. ammodendron and the basal diameter of H. persicum were the smallest; (2) Significant allometric scaling relationships were found between dry mass, total length, basal diameter, and each trait of assimilative branches, all of which were significantly less than 1; (3) The scaling exponents of the allometric relationship between four traits and the dry mass of assimilative branches of H. persicum were greater or significantly greater than those of H. ammodendron. The scaling exponents of the relationships between the basal diameter, dry mass, and total length of E. przewalskii were higher than those of the other three shrubs. Therefore, although different species have adapted to drought and high temperatures by convergence, there was great variability in morphological characteristics of assimilative branches, as well as in the scaling exponents of relationships among traits. The results of this study will provide valuable insights into the ecological functions of assimilative branches and survival strategies of these shrubs to cope with aridity and drought in desert environments.